Care of an undocumented immigrant: Case and comment - Beresford, H. Richard (Neurol Clin Pract, 2014)
This commentary addresses the care of an undocumented immigrant with neuromyelitis optica in the context of a state law designed to deny state-funded medical services to individuals whose presence in the United States is unlawful. It considers specific circumstances in which the law would permit or require medical care for undocumented persons in state medical facilities, including a duty to “stabilize” an “emergency medical condition” and the provision of care necessary to “protect life or safety.” It also addresses dilemmas clinicians may experience when faced with an apparent tension between their professional ethical obligations and legal rules aimed at enforcing immigration policies.